EXTERNAL RESPIRATION AND BLOOD GAS COMPOSITION IN CHILDREN WITH HEREDITARY HEMOLYTIC ANEMIA - K.I. ISMOILOV; M.S. KHUSENOVA (Avicenna Tajik State Medical University, 2024)
Objective: Investigation of the connection between the changes of the blood gas composition and external respiration (ER) disorders in children with hereditary hemolytic anemia (HHA) Methods: Forty-eight children with HHA hospitalized in the Pediatric Hematology Department of the National Medical Center of the Republic of Tajikistan "Shifobakhsh" (NMCRT) were examined. The patients were divided into three groups based on the severity of anemia: group 1 - 18 (37.5%) children with mild HHA, group 2 - 20 (41.7%) children with moderate HHA and group 3 - 10 (20.8%) children with severe HHA. The control group included 20 healthy children of comparable age and gender distribution. All patients with HHA underwent blood gas analysis and ER tests Results: There was no significant difference the blood acid-base status (ABS) between the children of the control and mild HHA groups: (pH - 7.36 [7.35; 7.36], pCO2 - 36.0 [35.3; 37.1], HCO3 - −24.8 [23.9; 24.5]) vs. (pH - 7.35 [7.35; 7.37], pCO2 - 39.4 [37.4; 40.6], HCO3 - − 22.8 [22.1; 23.6]) respectively. These parameters in children with moderate and severe HHA (pH - 7.32 [7.31; 7.33], pCO2 - 42.6 [41.8; 46.0], HCO3 - − 17.3 [17.0; 17.7]) and (pH - 7.28 [7.27; 7.29], pCO2 - 51.3 [50.3; 51.7], HCO3 - − 15.5 [14.8; 16.3]) respectively, were significantly different from the control group. Spirographic parameters in patients with moderate (Forced Expiratory Volume (FEV1 ) - 79.5 [79.5; 81.0], Tiffeneau index (TI) - 75.7 [74.9; 77.3], Forced Vital Capacity (FVC) - 78.4 [77.8; 80.6])} and severe anemia (FEV1 - 67.6 [66.8; 68.2], IT - 83.0 [83.8; 84.6], FVC - 66.0 [65.8; 68.2]) were significantly different from those with mild anemia (FEV1 - 82.3 [81.7; 83.8], TI - 75.8 [74.9; 76.8], FVC - 85.3 [84.2; 85.6]) and the control group (FEV1 - 86.9 [85.5; 88.3], IT - 75.2 [74.8; 75.9], FVC - 85.4 [84.5; 86.3]) Conclusion: The results of the study revealed pronounced changes in blood ABS and pulmonary ventilation disorder in children with a severe form of HHA